Um modelo DEA para avaliaç\~ao dos projetos eólicos offshore em licenciamento no Ibama - Jose Francisco Moreira Pessanha; Mário Jorge Mendonça; Albert Cordeiro Geber de Melo; Amaro Olimpio Pereira Júnior; Luis Alberto Toscano Medrano; Francisco José dos Santos Alves; Sidnei Costa Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The number and variety of offshore wind generation projects on the Brazilian coast points to the usefulness of an efficiency frontier, through which it is possible to identify projects that make the best use of resources. This work proposes a SBM-DEA model for evaluating offshore wind projects with licensing requests from the Brazilian Institute of the Environment and Renewable Natural Resources (Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis - Ibama).
Keywords: Q40; Q42; Q47; 330; wind power; offshore wind energy; data envelopment analysis